Covid-19 Pandemic's Effect on Performance and Acceleration of Performance Recovery: A Study on Manufacturing Industry in Bangladesh - Shahria, Golam (The International Journal of Accounting and Business Society, 2022)
Purpose – The main aim of this study is to examine the effect of the COVID-19 pandemic compared to the effects of the pandemic during and after this pandemic on manufacturing sectors in Bangladesh. In the aforementioned context, there are some issues taken as the specific objectives:  Methodology – The study is conducted on the manufacturing sectors listed under Dhaka Stock Exchange (DSE).  The study's target population is 42 manufacturing companies out of 153 listed on the Dhaka Stock Exchange (DSE). Four research variables were used to evaluate the financial performance and financial position of sample companies. Documentary analysis, descriptive analysis, data normality test, and Wilcoxon Signed–Rank Test are used to evaluate the hypothesis. The years of annual reports from 2018 - 2019 to 2020 – 2021 have been used for the documentary analysis of sample companies' financial performance and financial position. Findings – The study's conclusions demonstrate that this pandemic significantly impacted Bangladeshi companies' financial performance (essentially ROA and ROE) at a 5% level of significance compared to before the pandemic. The recovery growth rate of the financial performance of sample companies has been increased optimistically, and the growth of the liquidity position of manufacturing companies was also seen in good position after the COVID-19 pandemic compared to the COVID-19 pandemic based on the Wilcoxon statistical test tool. Practical implications—Considering that the COVID-19 epidemic has greatly impacted the import process of raw materials for production from China in particular and from other countries generally, the study advised the government of Bangladesh to boost its logistic and financial support for local raw materials facilities.  Originality/ Value—This study's findings can be used as a source of relevant data by investors or future investors for their investment decisions in the near future. The findings will assist the government in determining or preparing the appropriate tax incentive scheme for the impacted industries and whether the correct sector would profit from the scheme.